Atropoisomerismo: o efeito da quiralidade axial em substâncias bioativas Atropisomerism: the effect of the axial chirality in bioactive compounds - Anderson Rouge dos Santos; Alessandra Campbell Pinheiro; Ana Carolina Rennó Sodero; Andréa Sousa da Cunha; Monica Costa Padilha; Priscila Mesquita de Sousa; Silvia Paredes Fontes; Márcia Paranho Veloso; Carlos Alberto Manssour Fraga (Química Nova, 2007)
Atropisomerism is a special kind of stereoisomeric relationship that arises from the freezing of a certain conformation of an organic molecule, associated with a high rotational barrier about a single covalent bond. Atropisomerism has been originally described in orto-functionalyzed biphenyl derivatives, but a lot of other organic functionalities can present this structural phenomenon, characterized by the presence of chiral properties in compounds that don't present classical stereogenic centers. Atropisomeric compounds, intermediates and catalysts have well-know importance in organic synthesis, but the influence of the axial chirality in substances able to modulate biological systems is still not very exploited in drug design and development. In this context, the present account describes the importance of this structural property in the medicinal chemistry of different classes of bioactive compounds or therapeutic agents, emphasizing how atropisomerism could affect the molecular recognition of a ligand or a prototype by the target bioreceptor.